Studi Drilling Rate Index (DRI) Pada Batulempung dan Batupasir Formasi Balikpapan PT. RCI Job Site Abk Kecamatan Loajanan Kabupaten Kutai Kartanegara Provinsi Kalimantan Timur - Fadli Fadli; Agus Winarno; Tommy Trides (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Drilling is an essential operation in mining activities, particularly in borehole preparation for blasting purposes. The efficiency of blasting hole preparation depends significantly on the drilling speed to penetrate the rock formations.Drilling Rate Index (DRI) measures the ease or difficulty of drilling through rock formations. It combines two tests: Brittleness (S20) and SJ value. DRI serves as a common metric to predict drilling capabilities and is classified according to a table classification of drilling rate index.The classification of DRI values for sandstone and mudstone of Balikpapan Formation at PT. RCI Job Site ABK indicates a very high classification with DRI values ranging from 66 to 86. Testing results for samples SBP1 (DRI 75.9), SBP2 (DRI 81.7), SBL1 (DRI 66.6), and SBL2 (DRI 71.1) all fall within the very high classification range.